German prisoners of war in Britain, 1940-1948: Policy and performance. - Gillian S Clarke (2006)
Towards the end of the Second World War the British government embarked on an ambitious policy involving the large-scale employment of German prisoners of war in various sectors of the British economy, particularly in agriculture. By the autumn of 1946 it had succeeded in shipping more than 400,000 of these men to Britain from the Continent and America specifically for this purpose. Contrary to the requirement of the 1929 Geneva Convention, which stated that POWs should be repatriated 'as soon as possible after the conclusion of peace', thousands of these prisoners remained in this country as a supplementary labour force until 1948. Consequently, Britain's actions in this respect raise a number of important questions, which the present thesis seeks to address. Through an examination of a variety of primary source material, including official documents of the British and Canadian governments, parliamentary debates, commentary by contemporary informed observers, as well as a body of valuable secondary literature, it explains why officials believed that such a radical policy was necessary, the many practical difficulties that had to be overcome to bring it to fruition, and how, considering her international treaty obligations, Britain was able to justify legally the retention of POWs for three years after the war's end. Among the conclusions drawn is that Britain's POW policy was born of a selfish desire to alleviate a complex mixture of psychological, economic and political pressures, which came to bear on the country as a result of the war and its aftermath. Since the needs of the prisoners themselves were rarely taken into account, or what they, and others, felt to be their right to return to their homeland at the end of the war, the episode shows how British government officials were prepared to compromise Britain's moral standing in the wake of a global conflict which had, above all, been fought and won by the Allied powers on moral and ethical grounds.